Delayed Puberty Due to a WDR11 Truncation at Its N-Terminal Domain Leading to a Mild Form of Ciliopathy Presenting With Dissociated Central Hypogonadism: Case Report - Castro, Sebastián; Brunello, Franco G.; Sansó, Gabriela; Scaglia, Paula; Esnaola Azcoiti, María; Izquierdo, Agustín; Villegas, Florencia; Bergadá, Ignacio; Ropelato, María Gabriela; Martí, Marcelo A.; Rey, Rodolfo A.; Grinspon, Romina P. (Frontiers in Pediatrics, 2022)
Pubertal delay in males is frequently due to constitutional delay of growth and puberty, but pathologic hypogonadism should be considered. After general illnesses and primary testicular failure are ruled out, the main differential diagnosis is central (or hypogonadotropic) hypogonadism, resulting from a defective function of the gonadotropin-releasing hormone (GnRH)/gonadotropin axis. Ciliopathies arising from defects in non-motile cilia are responsible for developmental disorders affecting the sense organs and the reproductive system. WDR11-mediated signaling in non-motile cilia is critical for fetal development of GnRH neurons. Only missense variants of WDR11 have been reported to date in patients with central hypogonadism, suggesting that nonsense variants could lead to more complex phenotypes. We report the case of a male patient presenting with delayed puberty due to Kallmann syndrome (central hypogonadism associated with hyposmia) in whom the next-generation sequencing analysis identified a novel heterozygous base duplication, leading to a frameshift and a stop codon in the N-terminal region of WDR11. The variant was predicted to undergo nonsense-mediated decay and classified as probably pathogenic following the American College of Medical Genetics and Genomics (ACMG) criteria. This is the first report of a variant in the WDR11 N-terminal region predicted to lead to complete expression loss that, contrary to expectations, led to a mild form of ciliopathy resulting in isolated Kallmann syndrome.